A Comparative Study on the Performance of Single and Multi-Layer Encapsulated Phase Change Material Packed-Bed Thermocline Tanks - Huiqian Guo; ELSaeed Saad ELSihy; Zhirong Liao; Xiaoze Du (Energies, 2021)
This paper presents a numerical study that aims at investigating the effects of different parameters on the dynamic performance of single and multi-layer encapsulated phase material (PCM) thermocline tanks. A transient, one-dimensional, two-phase, concentric-dispersion model is formulated to evaluate such performance. Encapsulated paraffin waxes having different melting-points are used as PCMs, with water as heat transfer fluid. Comprehensive comparisons between single-PCM and multiple-PCMs systems are numerically analyzed first. Second, the effects of the PCM volume fraction (VF) and the inverse Stefan number have been discussed. The results show that among the various cases the single-PCM70 system has the highest performance in terms of charging and discharging efficiency, followed by a multiple-PCMs system with average performance. Compared with the PCM40 case, the PCM70 case has a 29% increase in the output energy from the system. The VF of PCMs influences the system output, both in terms of energy storage and release, the heat storage period and the total energy stored increased by 4.5%, when the VF of the PCM70 increases from 33.33% to 50%, respectively. Furthermore, it increases the system’s overall efficiency and total utilization ratio by 13.7% and 25%, respectively, when compared to the arrangement in which the PCM40 occupies 50% of the total bed height. The effect of the inverse Stefan number has a significant impact on the system’s utilization ratio. Compared with all other 3-PCM systems, the scenario with the lowest inverse Stefan number in the middle PCM has the highest charging and discharging efficiencies of 83.9% and 80.8%, respectively. The findings may be beneficial for the design and optimization of packed-bed tanks.